Is it possible to extend the dose interval of canakinumab treatment in children with familial Mediterranean fever? PeRA group experience - Gülşah Kavrul Kayaalp; Şengül Çağlayan; Fatma Gül Demirkan; Vafa Guliyeva; Gülçin Otar Yener; Kübra Öztürk; Ferhat Demir; Semanur Özdel; Mustafa Çakan; Hafize Emine Sönmez; Betül Sözeri; Nuray Aktay Ayaz (BMC, 2023)
Abstract Background There is no clear data on the optimal duration of treatment with anti-interleukin-1 drugs in colchicine-resistant familial Mediterranean fever patients, as well as on the dose interval. This study aimed to assess patients whose canakinumab dose interval was adjusted according to a specific protocol, with the objective of evaluating the effectiveness of implementing this protocol for the patient care. Methods The files of 45 patients whose canakinumab treatment interval was opened with a standard protocol previously determined by the Delphi method were retrospectively reviewed. Results Canakinumab treatment was initiated once a month for all patients. In the sixth month of canakinumab treatment, a dose interval extension was introduced; however, 7 patients (15.5%) experienced an attack, and consequently, no further interval extension was administered to them. For 29 patients, the dose interval was successfully extended to once every three months, as they remained attack-free for a year after the first interval extension. Nine patients continued receiving the drug every 2 months, as they had not yet completed one year since the first extension. The study found no significant correlation between experiencing an attack during the dose interval extension protocol and the number, duration of attacks, or autoinflammatory diseases activity index score. Conclusion Extending treatment intervals with canakinumab in colchicine-resistant familial Mediterranean fever shows promise for favorable outcomes.